Implementasi Model Inquiry-Based Learning Dalam Pembelajaran Fisika Untuk Meningkatkan Keterampilan Berpikir Kritis - Merianti (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2025)
This research is motivated by the low critical thinking skills of students in Physics learning which is often conventional and teacher-centered. The purpose of this study is to describe the implementation of the Inquiry-Based Learning (IBL) model and its effectiveness in improving students' critical thinking skills. This study uses a qualitative approach with a case study design conducted on 32 grade XI MIPA students at a public high school in Medan. Data collection was carried out through observation, critical thinking skills tests (pre-test and post-test), interviews, and documentation. Data were analyzed qualitatively-descriptively to describe the learning process and quantitatively using paired sample t-tests and N-Gain to measure improvement. The results showed that the implementation of the IBL model ran well and succeeded in improving students' critical thinking skills significantly (p < 0.05). This is evidenced by an increase in the average score from 48.5 to 76.2, with an N-Gain value of 0.54 which is included in the "moderate" category. Qualitatively, students showed an increase in active participation, argumentation skills, and scientific reasoning during the learning process. It is concluded that the Inquiry-Based Learning model is an effective learning strategy to empower students and develop their critical thinking skills in the context of complex Physics learning.